Relationship between endotoxin core and staphylococcal antibody levels and outcome following transcatheter aortic valve implantation (TAVI) - Andrew Smith; James Fullerton; John Whittle; James Moon; Michael Mullen; Paul Scully; Colin Hamilton-Davies (Perioperative Medicine)
Abstract Background Morbidity and mortality following aortic valve surgery is high. Low antibody levels to endotoxin core and to staphylococcus is associated with poor outcome following cardiac surgery. Transcatheter aortic valve implantation (TAVI) is an alternative treatment to surgery. This study examines the relationship between antibody levels and outcome following TAVI. Methods Using enzyme-linked immunosorbent assays (ELISA), we measured pre-procedure levels of antibodies to endotoxin core (EndoCAb) and 2 common staphylococcal epitopes on saved serum of 112 adult patients scheduled to undergo elective TAVI. Primary outcome measure was post-procedure length of stay (LOS) in hospital with secondary outcome being development of infective complications. Correlations were examined using Spearman rank order or Kendall Tau-b methods. Patients were quartiled according to antibody levels and outcomes compared between quartile groups. Differences between groups were examined using Student t-test, one-way ANOVA, and Kruskal–Wallis tests. Results One hundred twenty-two patients (64 M, 58 F) were recruited with mean age of 86 years. Little correlation was seen between any of the individual antibody levels or combined ranked antibody level with length of stay following TAVI (correlation coefficients—teichoic acid r 2 = 0.02, alpha-toxin r 2 = 0.02, EndoCAb r 2 < 0.02, combined rank r 2  = 0.03). When groups were quartiled, there was little difference between median length of stay across all quartiles for each antibody (ANOVA—teichoic acid p = 0.153, alpha-toxin p = 0.332, EndoCAb p = 0.848, combined rank p = 0.374). There were no differences in the number developing post-operative infections between the quartiles for each antibody type (ANOVA—teichoic acid p = 0.994, alpha-toxin p = 0.962, EndoCAb p = 0.918, combined rank p = 0.855). Conclusions This study indicates that there is little association between post-procedural length of stay in hospital following TAVI and pre-procedural antibody levels to endotoxin or staphylococcus, unlike that seen with surgical patients. Understanding this relationship may enable improved selection of therapeutic options for patients with impaired immunity needing aortic valve interventions. Trial registration The patients in this study are a sub-group of a larger observational cohort study looking at the prevalence of cardiac amyloid in the elderly with aortic stenosis in those patients undergoing transcatheter aortic valve replacement. ClinicalTrials.gov Identifier: NCT03029026.